Dated - Ho, Jia Fen (2016)
Dated is a 2D hand drawn animation film done by Tan Ping Hao, Melissa Sing, Wang Jia Ying and myself. Dated is about a character named Bob who lives in a world where having an octopus is a sign of old age. He tries to impress his date but his octopus does not make it easy. Is he fated to be dated.This report is about the process of making this film and the contributions made by each team member.